P58 Evidence of dendritic cell dysfunction in cirrhosis and its restoration by Toll-like receptor 4 antagonism. (16th November 2010) - Shah, N; Montes de Oca, M; Shah, N; Dhar, D; Davies, N; Mookerjee, R P; Jover-Cobos, M; Habtesion, A; Jalan, R
Abstract : Introduction: Infection complicates the course of cirrhosis and is the main cause of admission of patients to hospital. Recent studies have shown evidence of immune paralysis during severe decompensation. Our studies have suggested that neutrophil dysfunction in alcoholic hepatitis patients may be associated with a defect of TLR4 signalling, which is a key pathogen response receptor. Aim: The aims of this study were to characterise cellular immune function in a bile-duct ligated (BDL) model of cirrhosis and evaluate the role of TLR4 by using a selective antagonist, STM 28. (STM28 was kindly gifted by Professor Ken-ichi Tanamoto, Division of Microbiology, National Institute of Health Sciences, Tokyo 158-8501, Japan). Method: 18 C57BL/6 mice were studied: Sham operated, BDL (2 weeks after ligation) and BDL treated with TLR4 antagonist STM-28 (20 ug IP, 5 days). Peripheral blood was stained with fluorochrome-labellel antibodies specific for peripheral blood myeloid cells, dendritic cells (DC's, plasmocytoid and myeloid, expression of CD86 in myeloid); monocytes (residents and inflammatory); total granulocytes and neutrophils; CD4/CD8 T-cells and the expression of CD25 in CD4 T cell population; B cells and NK cells. Flow cytometric analysis was performed on a FACS Canto II. Biochemistry was measured spectrophotometrically. Results: A significant shift towards the myeloid subset of peripheral blood DCs was observed in BDL animals compared with sham (81% vs 54%, p=0.0002) accompanied by a significant decrease in the percentages of plasmocytoid DCs (2% vs 25%, p<0.0001), and an increased expression of CD86 in myeloid DC's (72% vs 55% p=0.05). There was an increase of TLR4 expression on monocytes and neutrophils (p=0.05). The percentage of CD3 T cell and CD8 T cell subpopulations were significantly lower only in BDL group (3% vs 14%, p=0.02; 1% vs 6%, p=0.02 respectively). No significant difference in NK cells was observed. TLR4 antagonist in BDL animals showed restoration towards plasmocytoid subset DCs, with a significant reduction in the percentage of myeloid DCs (67% vs 81%, p=0.003) but there was no significant difference in percentage of total myeloid cells, total granulocytes, neutrophils and monocyte populations. Liver function remained unaffected by the TLR4 antagonist. Conclusion: In cirrhosis, myeloid subtype DCs are expanded and there is relative depletion of plasmacytoid DC's and lymphophenia. Treatment with a TLR4 antagonist redresses a shift of dendritic cells from the myeloid back to plasmacytoid type. As the DC's play a pivotal role in antigen presentation, TLR4 antagonism may play an important therapeutic role in decreasing susceptibility of cirrhotic patients to infection.